The influence of the first goal on the final result of the football match - Leite, W. (Baltic Journal of Sport and Health Sciences, 2015)
Background. Among many technical and tactical aspects of the behaviour of players, the goals are the most studied. The goal is the key to success for teams and its analysis in all matches of a major football tournament that allows multiple assessments. Methods. The aim of this study was to analyze the influence of the first goal on the final result of the football match, identifying the team that scored the first goal and the final result obtained by this team: winning, drawing or losing, and subsequently, to relate the obtained results to physical, technical, tactical and psychological performance. We analyzed all the matches of the last 5 editions of the 6 major football tournaments (national teams) in the world: FIFA World Cup, UEFA Euro, CONMEBOL America Cup, AFC Asian Cup, CAF Africa Cup of Nations, and FIFA Confederations Cup (n = 996). The data were obtained from the database on the websites of the official federations, through overviews of the official matches. Quantitative data were collected in relation to the time that the goals were scored in the course of the matches. The statistical analysis of the results was conducted using the non parametric chi-square test. Results. According to the results, the team that scored the first goal in these last tournaments presented a high probability of winning (the average of 71.17% in the 6 tournaments). Conclusion. Thus, the high probability of victory in favour of the team that scores the first goal in the match of football is linked to the physical, technical, tactical and mainly the psychological aspects.